2017
DOI: 10.1007/s11600-017-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrical resistivity imaging (ERI) for the assessment of peat properties: a case study of the Całowanie Fen, Central Poland

Abstract: Complex studies were carried out to recognize the fen structure and peat properties in the Całowanie Fen area, belonging to the Natura 2000 network. The studies were conducted in two study areas that differ significantly in terms of peat thickness. Electrical resistivity imaging (ERI) was used to identify the properties of the peat and its substrate, such as thickness and electrical resistivity. Comparison of the field studies with the laboratory tests has shown that the ash content rises electrical resistivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
(35 reference statements)
4
19
0
Order By: Relevance
“…To the best of our knowledge, AEM has never been specifically applied before for the retrieval and characterization of boreal peatlands. As reported for other peatlands (Boon et al, 2008;Comas et al, 2015;Kowalczyk et al, 2017), in this case we find a resistive substrate underlying the peat. Developments of the AEM technology (better system monitoring and early time gates, e.g., Schamper et al, 2014) in the last decade have pushed it toward high-resolution near-surface deposits mapping (i.e., within the first 10 m of depth; Skurdal et al, 2018), making it potentially suitable for studying peatland characteristics, depth, and extension.…”
Section: 1029/2019gl083025supporting
confidence: 88%
See 3 more Smart Citations
“…To the best of our knowledge, AEM has never been specifically applied before for the retrieval and characterization of boreal peatlands. As reported for other peatlands (Boon et al, 2008;Comas et al, 2015;Kowalczyk et al, 2017), in this case we find a resistive substrate underlying the peat. Developments of the AEM technology (better system monitoring and early time gates, e.g., Schamper et al, 2014) in the last decade have pushed it toward high-resolution near-surface deposits mapping (i.e., within the first 10 m of depth; Skurdal et al, 2018), making it potentially suitable for studying peatland characteristics, depth, and extension.…”
Section: 1029/2019gl083025supporting
confidence: 88%
“…Ground electrical resistivity mapping has been also found successful in several applications (Boon et al, 2008;Comas et al, 2015;Elijah et al, 2012;Kowalczyk et al, 2017). Even though peat usually is electrically more resistive than the substrate (often clays), ground geophysical measurements have shown that there are several examples of peat over resistive unit, both in tropical environments (Comas et al, 2015) and in northern European countries (Boon et al, 2008;Kowalczyk et al, 2017). Even though peat usually is electrically more resistive than the substrate (often clays), ground geophysical measurements have shown that there are several examples of peat over resistive unit, both in tropical environments (Comas et al, 2015) and in northern European countries (Boon et al, 2008;Kowalczyk et al, 2017).…”
Section: 1029/2019gl083025mentioning
confidence: 99%
See 2 more Smart Citations
“…Correlations between peat thickness and soil surface elevation extracted from studies that report measurements recorded in locations situated in Asia, Africa, Europe, South, and North America. Data are extracted from the following sources: (a) – Cameron and Schruben () (dark red crosses: first bog to the left of “their figure ”, points 49‐5; blue triangles: third bog from the left of “their figure ” points 68‐16 – Maine, USA); (b) – Cubizolle et al () (France); (c) – Kowalczyk et al () (purple circles – Poland) and Silvestri et al () (orange squares – Norway); (d) – Esterle and Ferm () (“their figure ” – yellow circles – Indonesia); (e) – Esterle and Ferm () (“their figure ” – blue diamonds – Indonesia), Supardi and Neuzil () (“their figure ” – red squares – Indonesia), Page et al () (green crosses – Indonesia), Anshari, personal communication (purple triangles – Indonesia); (f) – Dargie et al () (Congo); (g) – Lähteenoja and Page () – (“their Figure a” – dark red squares – Peru and “their Figure b” – gray circles – Peru); (h) – Lähteenoja and Page () (“their Figure d” – Peru). The elevation is referred to a different zero for each data set, e.g., referred to the mean sea level or to another local reference as specified in the supporting information.…”
Section: Resultsmentioning
confidence: 99%